Likelihood of hospitalization for a chronic respiratory condition following pediatric infection with enterovirus and rhinovirus strains - Charlotte Switzer; Chris P. Verschoor; Kenneth Gavina; Dominik Mertz; Kathy Luinstra; Jeffrey M. Pernica; Marek Smieja (Infectious Medicine, 2022)
Background: Rhino-enteroviruses, particularly enterovirus strain D68 (EV-D68), have been associated with severe respiratory distress in children. The goal of this study was to compare the long-term outcomes of children with EV-D68 infection to that of children with other enterovirus / rhinovirus. Methods: Nasopharyngeal swabs from 174 children presenting with respiratory distress were tested by PCR for respiratory viruses. The primary outcome was diagnosis of a chronic respiratory condition within the follow-up period. Admission to intensive care, and length of stay were recorded. Odds ratios were determined using multinomial logistic regression. Results: During 5 years of follow-up, the crude odds of diagnosis with a chronic respiratory condition were significantly more likely in EV-D68 cases (OR: 1.95, 95% CI: 1.02, 3.82), but failed to remain significant after adjusting for a past history of asthma. Upon admission for a primary concern of asthma, length of stay both in hospital and intensive care were significantly longer in EV-D68 cases (OR: 2.10 [95% CI: 1.56, 2.82, p < 0.001]) and (OR: 5.18 [95% CI: 1.90, 6.28, p < 0.001]), respectively. After adjustment for a history of asthma, EV-D68 cases had significantly longer length of stay in hospital, admitted for 1.94 days for each day that controls were admitted (95% CI: 1.40, 2.68). In admissions to intensive care, EV-D68 cases spent 2.74 days for each day of admission in controls (95% CI: 1.62, 4.97, p < 0.001). Conclusions: Ours is first study to assess prognostic respiratory outcomes of patients infected with EV-D68 in childhood. Our study finds that EV-D68 cases were significantly more likely be hospitalized for longer than other enterovirus/rhinovirus controls in subsequent admissions for respiratory distress. Need for intensive care was significantly longer in EV-D68 infections. Our next steps will be validation in a larger sample size.